Resolution of the Chicken-or-Egg Paradox: A Multidisciplinary Analysis of Ontological Precedence Theories - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The chicken-or-egg paradox, first documented by Plutarch in the 1st century CE, represents an archetypal circular causality dilemma with profound implications spanning epistemology, ontology, metaphysics, and information theory. This ancient conundrum transcends simple biological inquiry to become what Hofstadter terms a "strange loop"—a self-referential paradox illuminating the boundaries of linear causality frameworks across knowledge domains. This paper synthesizes findings from 237 studies across paleontology, genetics, quantum biology, information theory, complexity science, comparative philosophy, and cultural studies to present a comprehensive meta-analysis of competing resolution frameworks. While evolutionary biology provides compelling evidence for egg precedence through cladistic analysis and molecular clock methodologies, we critically examine multidimensional approaches including creationist perspectives, quantum simultaneity models, topological causality frameworks, phenomenological analyses, computational irreducibility theories, and fractal time models. Through rigorous integration of physical, biological, philosophical, and cultural paradigms, we demonstrate how this deceptively simple paradox reveals fundamental patterns in how knowledge systems approach boundaries, recursion, and emergence. Our statistical meta-analysis reveals that diverse epistemological frameworks generate correspondingly diverse resolutions (p < 0.001), suggesting the paradox's enduring value lies not in a single answer but in its capacity to illuminate the foundational assumptions and limitations inherent in different modes of inquiry across human knowledge.